2016
DOI: 10.1242/jeb.141655
|View full text |Cite
|
Sign up to set email alerts
|

CCAP and FMRFamide-like peptides accelerate the contraction rate of the antennal accessory pulsatile organs (auxiliary hearts) of mosquitoes

Abstract: Insects rely on specialized accessory pulsatile organs (APOs), also known as auxiliary hearts, to propel hemolymph into their antennae. In most insects, this is accomplished via the pulsations of a pair of ampulla located in the head, each of which propels hemolymph across an antenna via an antennal vessel. Once at the distal end of the appendage, hemolymph returns to the head via the antennal hemocoel. Although the structure of the antennal hearts has been elucidated in various insect orders, their hormonal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 70 publications
1
6
1
Order By: Relevance
“…This independence is reminiscent of the independence between the dorsal vessel and another type of accessory pulsatile organ: the antennal heart. In both mosquitoes and cockroaches, there is no correlation between the contraction rate of the antennal hearts and the dorsal vessel, but different from what we observed for the wing heart, the antennal hearts contract at a significantly slower rate than the dorsal vessel (Hertel et al, 1985;Boppana and Hillyer, 2014;Suggs et al, 2016). Furthermore, some cardioacceleratory peptides, such as CCAP, FMRFamides and proctolin, are known to modulate the contraction dynamics of both the dorsal vessel and the antennal hearts of insects (Cuthbert and Evans, 1989;Predel et al, 2004;Ejaz and Lange, 2008;Hertel et al, 2012;Estevez-Lao et al, 2013;Suggs et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This independence is reminiscent of the independence between the dorsal vessel and another type of accessory pulsatile organ: the antennal heart. In both mosquitoes and cockroaches, there is no correlation between the contraction rate of the antennal hearts and the dorsal vessel, but different from what we observed for the wing heart, the antennal hearts contract at a significantly slower rate than the dorsal vessel (Hertel et al, 1985;Boppana and Hillyer, 2014;Suggs et al, 2016). Furthermore, some cardioacceleratory peptides, such as CCAP, FMRFamides and proctolin, are known to modulate the contraction dynamics of both the dorsal vessel and the antennal hearts of insects (Cuthbert and Evans, 1989;Predel et al, 2004;Ejaz and Lange, 2008;Hertel et al, 2012;Estevez-Lao et al, 2013;Suggs et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, the maximum acceleration of hemolymph is nearly 14 times greater when it exits the wing than when it enters it. For insects, data on hemolymph flow dynamics are sparse, but the data in the present study follow a comparable pattern to what we have observed for the antennal space of mosquitoes: velocity and maximum acceleration are highest near the contractile pump (Boppana and Hillyer, 2014;Suggs et al, 2016). In the case of the antennal heart, hemolymph velocity is fastest near the pump because the diameter of the antennal vessel that extends from the pump is narrower than the diameter of the antennal hemocoel into which it empties.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Still in L. migratoria, CCAP-like immunostained cells were discovered in the fat body associated with the oviducts that represents a potential source of CCAP, along the transverse nerve and perivisceral organs. In the mosquito A. gambiae, CCAP increased the contraction rate of the auxiliary hearts, the organ that controls hemolymph circulation in the antennae (Suggs et al, 2016). In S. officinalis CCAPs increased the vena cava tonus in a dose-dependent manner; this demonstrates their involvement in the regulation of hemolymph circulation (data not shown).…”
Section: Discussionmentioning
confidence: 85%
“…One example is the excitatory action of FaRPs in chromatophore neuromuscular junctions of the cuttlefish Sepia officinalis (Loi and Tublitz 2000, see discussion). In auxiliary hearts of mosquitoes that propel hemolymph into the antennae of the insects FaRPs have accelerating effects (Suggs et al, 2016). Although the presence of FaRPs has been described in the visual system and along mechanosensory neurons of C. salei, Schmid 1999, Fabian-Fine et al, 2017) the distribution of these neuropeptides throughout the rest of the spider nervous system has not been described in detail.…”
Section: Introductionmentioning
confidence: 99%